Comprehensive analysis of multimedia storytelling in the modern information space - Olga Muravyova4, Asima Ishanova5Mariyamgul Kussainova1, Lazzat Kozhakhmetova2, Meruert Kumarova3, (Opción, 2019)
The object of this study is multimedia storytelling (as a genre) and its formats in Kazakhstan and French media practice. The theoretical basis of the study was the monographs and scientific articles of Kazakhstan and French modern media researchers on new digital formats of journalism as a . As a result, the percentage of stories where there are heroes in the text in the Kazakh and French media is not very different. In conclusion, storytelling’s main characteristics should be considered the obligatory presence of history on a relevant topic and interpretation of history through the prism of the author’s perception.